Identification of canonical pyroptosis-related genes, associated regulation axis, and related traditional Chinese medicine in spinal cord injury - Shan, Wenshan; Li, Shuang; Yin, Zongsheng (Frontiers in Aging Neuroscience, 2023)
Neuroinflammation plays an important role in spinal cord injury (SCI) and pyroptosis is an inflammatory - related programmed cell death. Although neuroinflammation induced by pyroptosis has been reported in SCI, there is a lack of systematic research on SCI pyroptosis and its regulation mechanism. The purpose of this study was to systematically analyze the expression of pyroptosis related genes (PRGs) in different SCI models and associated regulation axis by bioinformatics methods. We downloaded raw counts data of seven high-throughput sequencing and two microarray datasets from the GEO database, classified by species (rat and mouse) and SCI modes (moderate contusive model, aneurysm clip impact-compression model and hemisection model), including mRNAs, miRNAs, lncRNAs, and circRNAs, basically covering the acute, subacute and chronic stages of SCI. We performed differential analysis by R (DEseq2) or GEO2R and found that the AIM2/NLRC4/NLRP3 inflammasome related genes, GSDMD, IL1B and IL18 were highly expressed in SCI. Based on the canonical NLRP3 inflammasome-mediated pyroptosis related genes (NLRP3/PRGs), we constructed transcription factors (TFs) - NLRP3/PRGs, miRNAs- Nlrp3/PRGs and lncRNAs/circRNAs/mRNAs - miRNA- Nlrp3/PRGs (ceRNA) networks. In addition, we also predicted Traditional Chinese medicine (TCM) and small, drug-like molecules with NLRP3/PRGs as potential targets. It is expected to provide new ideas and therapeutic targets for the treatment of SCI.